Antimicrobial resistance: One health approach in Rwanda - Sindayigaya, Patience; Rinda Ubuzima (My University, 2024)
This commentary provides the authors' views related to the Antimicrobial Resistance (AMR) profile in Rwanda in terms of prevalence, knowledge, attitudes, practices, and existing interventions at the one health interface. AMR is a critical and global health concern posing a significant threat to the effective treatment of infections and lead to increased morbidity and mortality. Among few studies that have been conducted on AMR in Rwanda, the issue was found to be widespread in both human and animals. A high resistance has been found among the commonly used antibiotics seconded by the lack of knowledge and appropriate practices among different groups of people. Some interventions, including “one health” approach are in place aiming to address these issues, but challenges are still around due to developing surveillance system, limited studies, and low public awareness. Extensive studies and enhance surveillance are recommended to better understand AMR to inform the public and policy makers for effectively tackling of the AMR issue, particularly in rural areas.
Keywords: Antimicrobial resistance; Rwanda; Usage; impact; Global Health Security